Effect of Cosmetics Use on the In Vitro Skin Absorption of a Biocide, 1,2-Benzisothiazolin-3-one - Yoonjung Huh; Do-Hyeon Lee; Dalwoong Choi; Kyung-Min Lim (Toxics, 2022)
1,2-Benzisothiazolin-3-one (BIT) is a commonly used organic biocide containing an isothiazolone ring. However, it may have adverse effects on human health and its risk needs to be properly evaluated. Dermal exposure is the main route of BIT exposure, and co-exposed substances may affect its absorption. The dermal permeation profile of BIT has not been well-studied. This study aimed to investigate the dermal permeation profiles of BIT with or without cosmetic use. Dermal permeation profiles of BIT were investigated after infinite- (100 μg/cm2), or a finite-dose (10 μg/cm2) application with or without cosmetics using a minipig skin and Strat-M®, an artificial membrane. A cream, lotion, and essence (namely, face serum) were pre-treated as representative cosmetics on minipig skin for 30 min, with BIT treatment afterward. After the treatment, BIT left on the skin surface was collected by cotton swabbing, BIT in the stratum corneum, by sequential tape stripping, and BIT retained in the remaining skin was extracted after cutting the skin into pieces before LC-MS/MS analysis. When an infinite dose was applied, permeation coefficients (Kp, cm/h) for minipig skin and Strat-M® were 2.63 × 10−3 and 19.94 × 10−3, respectively, reflecting that skin permeation was seven to eight times higher in Strat-M® than in the minipig skin. BIT, in the presence of cosmetics, rapidly permeated the skin, while the amount in the stratum corneum and skin deposit was reduced. We performed a risk assessment of dermally applied BIT in the absence or presence of cosmetics by calculating the skin absorption rate at 10 h based on the toxicological data from several references. The risk level was higher in the presence of essence as compared to lotion, which was higher than cream, which was higher than the control (non-treated). However, all of the margins of safety values obtained were greater than 100, suggesting that BIT is safe for use in dermally exposed consumer products. We believe that this research contributes to a greater understanding of the risk assessment of isothiazolinone biocides.